Analysis of potential GHG emissions reductions from methane recovery in livestock farming. (2015) - Gallo, Michela; Borghi, Adriana Del; Strazza, Carlo
Livestock farming is a significant source of greenhouse gases (GHG) owing to the high amount of methane emissions. The purpose of this paper is to present an analysis of the potential emission reductions and their enhancement during manure management through the optimisation of the main parameters involved, such as temperature, manure characteristics, type of management system. The investigation of a swine manure management system is performed with calculation of GHG emissions reduction due to a methane recovery system coupled with on-site power generator. The analysis conducted on the three parameters considered shows a variation of the methane emissions from 390 (drylot) to 31, 000 tCO2e /year (anaerobic lagoon or liquid/slurry). The findings demonstrate that the substitution of anaerobic lagoon systems with a methane recovery system can be considered as a promising process in terms of GHG emissions reduction also in case of not highly favourable conditions of temperature and manure characteristics.